Reinforcing and Improving the Behavior of Reinforced Concrete Slabs Employing the Optimal Amount of Polymer Fibers and Examining the Effect of the Number of Fiber Layers - Sina Bashiri, Mehdi khoshvatan (International Journal of Modern Agriculture, 2020)
Reinforcing and increasing the bearing capacity of concrete slabs can increase the flexural and shear capacity of the structure, and it plays an important role in the behavior of structures because of using slabs in structures such as buildings and bridges. In this paper, reinforced concrete slabs' behavior has been reinforced and improved using the optimal amount of polymer fibers and examining the effect of the number of fiber layers. Modeling was performed in Abaqus software, and nonlinear static analysis was applied. The results showed that reinforced concrete slabs' reinforcement increases the amount of final displacement at the moment of rupture, and the reinforced slabs bear more displacement. Slabs reinforced with carbon fibers add about 9%, slabs reinforced with aramid fibers 6, and glass fibers about 4% to the final displacement rate. Carbon fibers have the greatest influence on this parameter, and aramid and glass fibers are in the next levels. Additionally, the rate of energy absorption in the concrete slab is increased after reinforcement. The energy absorption rate of carbon fiber and aramid-reinforced models is increased by approximately the same amount and about 7%. The glass-fiber-reinforced model also is improved in energy absorption by approximately 2%. The final displacement rate in models reinforced with a 2 mm thick plate presents an increase in the final displacement rate at the moment of rupture compared to the non-reinforced model. If carbon fiber is utilized, the final displacement rate will be increased by nearly 23%. The aramid and glass fibers are increased by 17 and 12%, respectively. The model with a carbon fiber reinforcement sheet in models with a 2 mm thick reinforcement sheet has the highest amount of energy absorption, which increases by 23%. In the model with aramid fiber reinforcement sheet, this amount is about 18, and it is increased by 8% with glass fibers.